2007
DOI: 10.1074/jbc.m607298200
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3F Can Inhibit the Accumulation of HIV-1 Reverse Transcription Products in the Absence of Hypermutation

Abstract: APOBEC3F (apolipoprotein B mRNA-editing enzyme catalytic polypeptide 1-like protein 3F) is a cytidine deaminase that, like APOBEC3G, is able to restrict the replication of HIV-1/delta vif. Initial studies revealed high numbers of mutations in the cDNA of viruses produced in the presence of these proteins, suggesting that cytidine deamination underpinned the inhibition of infection. However, we have recently shown that catalytically inactive APOBEC3G proteins, derived through mutation of the C-terminal cytidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
294
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(332 citation statements)
references
References 58 publications
(58 reference statements)
32
294
1
2
Order By: Relevance
“…In our own study, comparable inhibition of HIV-1 infectivity by wt and deaminase-defective APO3G required higher levels of the enzymatically inactive protein, leading us to conclude that wt APO3G had stronger antiviral potential than its deaminasedefective counterpart (30). Similar conclusions were drawn by Holmes et al (12). The requirement for high levels of virusassociated deaminase-defective APO3G for virus inhibition is reminiscent of one of our previous studies, in which we noted that the HIV-1 Vif protein, when packaged at supraphysiological levels into HIV-1 virions, had strong antiviral activity (2).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our own study, comparable inhibition of HIV-1 infectivity by wt and deaminase-defective APO3G required higher levels of the enzymatically inactive protein, leading us to conclude that wt APO3G had stronger antiviral potential than its deaminasedefective counterpart (30). Similar conclusions were drawn by Holmes et al (12). The requirement for high levels of virusassociated deaminase-defective APO3G for virus inhibition is reminiscent of one of our previous studies, in which we noted that the HIV-1 Vif protein, when packaged at supraphysiological levels into HIV-1 virions, had strong antiviral activity (2).…”
Section: Discussionsupporting
confidence: 88%
“…Some of these effects do not require catalytically active APO3G (19,22), and several reports suggested that deaminase-defective APO3G and APO3F have antiviral activity when transiently coexpressed with HIV-1 in 293T cells (3,12,28,35). Our own data concerning the antiviral properties of the deaminase-defective APO3G C288S/C291A mutant supported these conclusions (30).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The packaged APOBEC3 proteins inhibit infection in target cells by deaminating deoxycytidine residues on the DNA minus strand during reverse transcription, inducing hypermutation in newly synthesized HIV-1 DNA. APOBEC3 proteins also inhibit replication by cytidine deaminase-independent mechanism(s), such as blocking reverse transcription (18)(19)(20)(21). Vif binds several APOBEC3 proteins and targets them for ubiquitinylation and degradation in the proteasome in virus producer cells, thereby blocking the antiviral activity (22).…”
mentioning
confidence: 99%
“…Incorporated A3G specifically deaminates cytosine residues to uracil in growing singlestranded DNA during reverse transcription, leading to HIV genome degradation or hypermutation (5,25,39,48,49,98). More recent studies indicate that deaminase-independent mechanisms might also be involved in antiviral activity of A3 (4,27,28,30,54,61). The amount of encapsidated A3G in wild-type (wt) HIV-1 virions is dramatically reduced by a Vifdependent degradation via the ubiquitination-proteasome pathway (50,79,94,95).…”
mentioning
confidence: 99%